Identification and distribution of mating‐type idiomorphs in populations of Podosphaera macularis and development of chasmothecia of the fungus. (19th February 2015) - Wolfenbarger, S. N.; Twomey, M. C.; Gadoury, D. M.; Knaus, B. J.; Grünwald, N. J.; Gent, D. H.
Abstract : Podosphaera macularis, the causal agent of hop powdery mildew, is known to produce chasmothecia (formerly cleistothecia) in eastern North America and Europe. Ascocarps have not yet been reported from the Pacific Northwestern region of North America. Reasons for the apparent absence of chasmothecia in the Pacific Northwest were unknown. This study established that P . macularis is heterothallic and ascocarp ontogeny, maturation, dehiscence and ascospore infection proceed similarly to other powdery mildew fungi. Genome sequencing of a MAT1‐1 isolate revealed the structure of the MAT1 locus and presence of MAT1‐1‐3, demonstrating further similarities to other powdery mildew fungi. PCR assays with primers designed from conserved domains of the MAT1 idiomorphs were developed to characterize the frequency of idiomorphs in populations of P. macularis . Amongst 317 samples of P. macularis collected during 2012 and 2013 from the Pacific Northwest only the MAT1‐1 idiomorph was found. In contrast, among 56 samples from the eastern United States and Europe, MAT1‐1 and MAT1‐2 idiomorphs were detected at equivalent frequencies. At temperatures representative of late season conditions in the Pacific Northwest, chasmothecia formed readily when a Pacific Northwest MAT1‐1 isolate was paired with a MAT1‐2 isolate collected from outside the region. Although these findings do not encompass all climatic, geographic or temporal barriers that could inhibit the formation of chasmothecia, the current absence of the ascigerious stage of P . macularis in the Pacific Northwest could be explained by the absence of the MAT1‐2 mating type idiomorph.